Relationship Between Active Faulting/Fracturing and Magmatism Around Santorini: Seismic Anisotropy From an Active Source Tomography Experiment. Issue 8 (8th August 2021) - Heath, B. A.; Hooft, E. E. E.; Toomey, D. R.; Paulatto, M.; Papazachos, C. B.; Nomikou, P.; Morgan, J. V.
Abstract: In extending volcanic arcs such as the Aegean, tectonic processes exert a significant control on magmatism. Spanning scales from 1 to 10s of km, volcanic vents, edifices, and eruptive centers follow the orientation of, and are located near, fault zones. Whether this tectonic control on magmatism results from individual faults/fractures weakening the crust or because regional stresses control magma input into the crust is debated. Here we investigate the scales of tectonic and magmatic interactions, specifically focusing on the role of local‐scale (<10 km) faults/fractures in controlling magmatism. We infer local‐scale fault/fracture orientations from anisotropic active‐source P‐wave travel‐time tomography to investigate tectonic and magmatic interactions in the upper crust of Santorini Volcano, Greece, and the actively deforming region to the east. We use the anisotropy magnitude and seismic velocity reduction to model the relative distribution of both consistently oriented and randomly oriented faults/fractures. Our results show that oriented faulting/fracturing resulting from regional‐scale (>10 km) tectonic stresses is distributed broadly across the region at 2–3 km depth, approximately paralleling volcanic/magmatic features. On a local‐scale, magmatism is neither localized in areas of higher oriented fault/fracture density, nor is it accommodating enough extensional strain to inhibit oriented faulting/fracturing of host rock. The alignment of magmatic features shows strong tectonic control despite the lack of correlation with local oriented fault/fracture density. These results suggest that magmatic processes are strongly influenced by regional‐scale, not local‐scale, tectonic processes. We infer regional processes have a greater impact on magmatism than local features due to their greater effect at depth. Plain Language Summary: Magmatic features are often preferentially located near, and share the same orientation as, faults and fractures. These faults/fractures, which weaken the upper crust, span a variety of scales from meters to 10s of kilometers. It is not clear which tectonic feature‐scale dominates the relationship between magmatic and tectonic (faults/fractures) interactions. Here we use a seismic experiment at Santorini Volcano, Greece, to investigate tectonic controls on magmatism. We use the directional dependence of seismic velocity, whether seismic waves travel faster in one direction over another, in addition to results from previous studies to investigate the lateral distribution and orientation of faults/fractures. Fault/fracture orientations across a variety of scales are found to parallel the orientation of magmatic features, suggesting tectonic structures do impact magmatism. However, we find no evidence that there are more faults/fractures near magmatic centers (i.e., the upper crust is not abnormally weak), but rather find that faults/fractures are regionally pervasive. We hypothesize that both magmatic and tectonic features are responding to broad‐scale, regional tectonic stresses and structures. These broad‐scale stresses and structures have a greater effect at depth, and therefore dominate magmatic/tectonic interactions, suggesting that not all faults/fractures have the same impact on magmatism. Key Points: Local crack orientation and distribution are recovered by anisotropic P‐wave travel‐time tomography Porosity from local, oriented cracks is uncorrelated with regions of volcanic activity at 2–3 km depth Magmatic processes are controlled by regional tectonic stresses, not local cracks and stresses